1999
DOI: 10.1182/blood.v94.1.87.413k41_87_96
|View full text |Cite
|
Sign up to set email alerts
|

GATA-1 and Erythropoietin Cooperate to Promote Erythroid Cell Survival by Regulating bcl-xL Expression

Abstract: The transcription factor GATA-1 is essential for normal erythropoiesis. By examining in vitro–differentiated embryonic stem cells, we showed previously that in the absence of GATA-1, committed erythroid precursors fail to complete maturation and instead undergo apoptosis. The mechanisms by which GATA-1 controls cell survival are unknown. Here we report that in erythroid cells, GATA-1 strongly induces the expression of the anti-apoptotic protein bcl-xL, but not the related proteins bcl-2 and mcl-1. Consistent w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
140
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(156 citation statements)
references
References 54 publications
7
140
0
5
Order By: Relevance
“…Thus, expressions of these proteins are involved in cell survival and proliferation of bone marrow progenitor cells with erythroid differentiation potential during the stress response. The striking positive correlation observed among EPO-R, GATA-1, and Bcl-x L are in agreement with a previous report (Gregory et al, 1999): this suggests that a particular intrinsic recovery program is suitable in bone marrow erythroid cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, expressions of these proteins are involved in cell survival and proliferation of bone marrow progenitor cells with erythroid differentiation potential during the stress response. The striking positive correlation observed among EPO-R, GATA-1, and Bcl-x L are in agreement with a previous report (Gregory et al, 1999): this suggests that a particular intrinsic recovery program is suitable in bone marrow erythroid cells.…”
Section: Discussionsupporting
confidence: 93%
“…EPO-EPO-R signaling results in the survival, proliferation, and differentiation of erythroid progenitors (Jelkmann, 2004). Like EPO and EPO-R, GATA-1 serves an antiapoptotic function by regulating the expression of Bcl-x L required for erythroid cell survival (Gregory et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified an association between aberrant methylation of the 5¢cis-regulatory region of GATA1 with a failure to up-regulate its gene expression during erythropoiesis in MDS lower and higher risk patients. GATA1 is critical for erythroid differentiation and could be called 'erythroid master gene' (7,22,(70)(71)(72). A previous study already associated dysregulated GATA1 expression with an arrest in primitive erythroid cell development (73) and with an erythroid maturation block in low-risk MDS (6).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-XL acts by preventing the release of pro-apoptotic molecules from mitochondria (Gregoli and Bondurant, 1999). The transcription factor GATA-1 is involved in Epo-mediated up-regulation of Bcl-XL (Gregory et al, 1999) and positively regulates expression of erythroid genes (Pevny et al, 1991). This transcription factor is a target for caspases in cells undergoing death upon Epo starvation or induction of death receptor Fas (De Maria et al, 1999;Gregoli and Bondurant, 1999), but it remains uncleaved during cell differentiation stimulated with Epo (Zermati et al, 2001;Carlile et al, 2004).…”
Section: Discussionmentioning
confidence: 99%